MULTIPLICATION COMPONENTS OF GRADED MODULES - Abu-Dawwas, Rashid (Italian Journal of Pure and Applied Mathematics, 2015)
Let G be a group and g ∈ G. Let R be a commutative G-graded ring and M be a graded R-module. In this paper, we study some cases when R is strongly graded ring and the component Me of M is multiplication Re-module. Also, we prove that if R is strongly graded, then the components Mg of M are multiplication Re-modules if and only if the component Me is P-torsion or P-cyclic where P is a prime ideal of the component Re of R.